Deepfaking Keanu: YouTube deepfakes, platform visual effects, and the complexity of reception. (August 2021) - Bode, Lisa
On July 14, 2019, a 3-minute 36-second video titled "Keanu Reeves Stops A ROBBERY!" was released on YouTube visual effects (VFX) channel, Corridor. The video's click-bait title ensured it was quickly shared by users across platforms such as Facebook, Twitter, and Reddit. Comments on the video suggest that the vast majority of viewers categorised it as fiction. What seemed less universally recognised, though, was that the performer in the clip was not Keanu Reeves himself. It was voice actor and stuntman Reuben Langdon, and his face was digitally replaced with that of Reeves, through the use of an AI generated deepfake, an open access application, Faceswap, and compositing in Adobe After Effects. This article uses Corridor's deepfake Keanu video (hereafter shorted to CDFK) as a case study which allows the fleshing out of an, as yet, under-researched area of deepfakes: the role of framing contexts in shaping how viewers evaluate, categorise, make sense of and discuss these images. This research draws on visual effects scholarship, celebrity studies, cognitive film studies, social media theory, digital rhetoric, and discourse analysis. It is intended to serve as a starting point of a larger study that will eventually map types of online manipulated media creation on a continuum from the professional to the vernacular, across different platforms, and attending to their aesthetic, ethical, cultural and reception dimensions. The focus on context (platform, creator channel, and comments) also reveals the emergence of an industrial and aesthetic category of visual effects, which I call here "platform VFX, " a key term that provides us with more nuanced frames for illuminating and analysing a range of manipulated media practices as VFX software becomes ever more accessible and lends itself to more vernacular uses, such as we see with various face swap apps.